Gut dysbiosis in Huntington's disease: associations among gut microbiota, cognitive performance and clinical outcomes. Issue 2 (24th July 2020) - Wasser, Cory I; Mercieca, Emily-Clare; Kong, Geraldine; Hannan, Anthony J; McKeown, Sonja J; Glikmann-Johnston, Yifat; Stout, Julie C
Abstract: Huntington's disease is characterized by a triad of motor, cognitive and psychiatric impairments, as well as unintended weight loss. Although much of the research has focused on cognitive, motor and psychiatric symptoms, the extent of peripheral pathology and the relationship between these factors, and the core symptoms of Huntington's disease, are relatively unknown. Gut microbiota are key modulators of communication between the brain and gut, and alterations in microbiota composition (dysbiosis) can negatively affect cognition, behaviour and affective function, and may be implicated in disease progression. Furthermore, gut dysbiosis was recently reported in Huntington's disease transgenic mice. Our main objective was to characterize the gut microbiome in people with Huntington's disease and determine whether the composition of gut microbiota are significantly related to clinical indicators of disease progression. We compared 42 Huntington's disease gene expansion carriers, including 19 people who were diagnosed with Huntington's disease (Total Functional Capacity > 6) and 23 in the premanifest stage, with 36 age- and gender-matched healthy controls. Participants were characterized clinically using a battery of cognitive tests and using results from 16S V3 to V4 rRNA sequencing of faecal samples to characterize the gut microbiome. For gut microbiome measures, we found significant differences in the microbial communities (beta diversity) based on unweighted UniFrac distance ( P  =   0.001), as well as significantly lower alpha diversity (species richness and evenness) between our combined Huntington's disease gene expansion carrier group and healthy controls ( P  =   0.001). We also found major shifts in the microbial community structure at Phylum and Family levels, and identified functional pathways and enzymes affected in our Huntington's disease gene expansion carrier group. Within the Huntington's disease gene expansion carrier group, we also discovered associations among gut bacteria, cognitive performance and clinical outcomes. Overall, our findings suggest an altered gut microbiome in Huntington's disease gene expansion carriers. These results highlight the importance of gut biomarkers and raise interesting questions regarding the role of the gut in Huntington's disease, and whether it may be a potential target for future therapeutic intervention. Abstract : Emerging evidence links the gut–brain axis to neurodegenerative diseases. Wasser et al. report the first evidence of gut dysbiosis in people with Huntington's disease. Their results highlight the importance of gut biomarkers and the prospect of future therapeutic interventions in Huntington's disease. Graphical Abstract: